Elimination of Purkinje Fibers by Electroporation Reduces Ventricular Fibrillation Vulnerability - Christopher Livia; Alan Sugrue; Tyra A. Witt; Murray Polkinghorne; Elad Maor; Suraj Kapa; H. Immo Lehmann; Christopher V. DeSimone; Atta Behfar; Samuel J. Asirvatham; Christopher J. McLeod (2018)
Background The Purkinje network appears to play a pivotal role in the triggering as well as maintenance of ventricular fibrillation. Irreversible electroporation ( IRE ) using direct current has shown promise as a nonthermal ablation modality in the heart, but its ability to target and ablate the Purkinje tissue is undefined. Our aim was to investigate the potential for selective ablation of Purkinje/fascicular fibers using IRE . Methods and Results In an ex vivo Langendorff model of canine heart (n=8), direct current was delivered in a unipolar manner at various dosages from 750 to 2500 V, in 10 pulses with a 90-μs duration at a frequency of 1 Hz. The window of ventricular fibrillation vulnerability was assessed before and after delivery of electroporation energy using a shock on T-wave method. IRE consistently eradicated all Purkinje potentials at voltages between 750 and 2500 V (minimum field strength of 250-833 V/cm). The ventricular electrogram amplitude was only minimally reduced by ablation: 0.6±2.3 mV ( P=0.03). In 4 hearts after IRE delivery, ventricular fibrillation could not be reinduced. At baseline, the lower limit of vulnerability to ventricular fibrillation was 1.8±0.4 J, and the upper limit of vulnerability was 19.5±3.0 J. The window of vulnerability was 17.8±2.9 J. Delivery of electroporation energy significantly reduced the window of vulnerability to 5.7±2.9 J ( P=0.0003), with a postablation lower limit of vulnerability=7.3±2.63 J, and the upper limit of vulnerability=18.8±5.2 J. Conclusions Our study highlights that Purkinje tissue can be ablated with IRE without any evidence of underlying myocardial damage.